Influence of residual chlorine and pressure on degradation of polybutylene pipe. (September 2019) - Fujii, Takehiro; Matsui, Yuichi; Hirabayashi, Hideo; Igawa, Kazuhisa; Okada, Saori; Honma, Hidekazu; Nishimura, Hiroyuki; Yamada, Kazushi
Abstract: In this paper, we report a novel technique that enabled us to easily and effectively conduct an accelerated degradation test on a small pressure vessel for potable and hot water pipes. Accelerated degradation tests were carried out on polybutene (PB) pipes with and without pressurization, under chlorinated and non-chlorinated water at 80 °C; the higher-order structure changes, residual antioxidant agents, and degradation characteristics of the PB pipes were evaluated. In the degradation test under chlorine water, the isothermal oxidation induction time (I-OIT) time and the mechanical properties decreased with increasing aging time. Additionally, micro- Fourier transform infrared spectroscopy (FT-IR) imaging revealed the distribution of antioxidants in the PB pipe before and after the test, while in the degradation test under pressure, the residual amount of antioxidants was smaller, and the chemiluminescence intensity was higher compared with the test that was not pressurized. These results strongly suggest that not only dissolved chlorine but also water pressure contribute to promoting the degradation of plastic pipes, and that the simple pressure vessels allow the safe and easy testing of accelerated degradation. Highlights: Accelerated degradation tests were conducted for Polybutylene pipe. Influence of residual chlorine and pressure on degradation of polybutylene pipe are examined. The degradation of the PB pipe was promoted by chlorine derivatives. The degradation of the PB pipe was accelerated due to decreasing amount of the antioxidant even under water pressure.